The Effect of Yoga Exercise on Anxiety Levels Primigravida Third Trimester Pregnant Women in PMB Eny Islamiati Bululawang Malang - Silviana Wahidah Hilmiy; Rosyidah Alfitri; Sulistiyah Sulistiyah (Knowledge Dynamics, 2024)
Background: Pregnancy is a significant and indelible experience in a woman's life. Pregnancy has the potential to become an emotional upheaval for certain women. If not properly handled, it can lead to issues for both the mother and the newborn. Substantial data indicates a strong correlation between pregnancy and various psychological issues among expectant mothers, such as worry, anxiety, and sadness. Physical exercise, such as meditation or yoga, is a treatment used to decrease anxiety in pregnant women. The aim of this study was to assess the impact of prenatal yoga on the anxiety levels of primigravida pregnant women in the third trimester at PMB Eny Islamiati Bululawang Malang. Methods: This research employs quantitative methodologies with a pre-experimental design utilizing a one-group pretest post-test design. Specifically, it involves studying a single group of individuals and measuring their characteristics both before and after receiving therapy. Results: The study revealed that all 16 respondents encountered anxiety before the session. Following the administration of partial intervention, 43.8% of the respondents reported no anxiety, 43.8% reported mild anxiety, and 12.5% reported moderate anxiety. Subsequently, a p-value was obtained, indicating that exercise affects anxiety levels. The impact of yoga on anxiety levels of primigravida pregnant women in their third trimester will be studied at PMB Eny Islamiati Bululawang Malang. Conclusions: The researchers found significant variations in anxiety levels among Primigravida III Trimester pregnant women before and after participating in yoga exercises at PMB Eny Islamiati Bululawang, Malang Regency